SISTEM PENGAJARAN BAHASA ARAB MODERN UNTUK NON -ARAB - Maria Ulfa (Institut Agama Islam Negeri (IAIN) Metro, 2018)
One of the fundamental weaknesses of Arabic language teaching system in non-Arab circles, especially in Indonesia, is the weakness of the teaching curriculum that is applied. In all its aspects, especially the vision and methodology, the existing curriculum generally teaches Arabic with a traditional orientation, ie for religious purposes with accentuation on aspects of grammar mastery and translation skills. For the present time, the teaching system with such curriculum model is no longer relevant and therefore must be in the fox immediately. Because, when referring to the development of today's Arabic language as an international language is no longer only functioning as a religious language. But it has become a medium of communication all aspects of life. Consequently, Arabic is no longer sufficient to be mastered only passively in the form of grammar mastery and translation skills, but must be communicated in a broader sense, both spoken and written. Therefore, the Arabic language teaching system has been developed with a modern oriented teaching curriculum. It is a well-designed curriculum with complete content and elements as a teaching system as well as teaching Arabic language for the purpose of supporting its role in today's day. Salah satu kelemahan mendasar system pengajaran bahasa arab di kalangan non arab terutama di Indonesia, adalah lemahnya kurikulum pengajaran yang di terapkan. Dalam segenap aspeknya, terutama visi dan metodologi, kurikulum yang ada pada umumnya mengajarka bahasa arab dengan orientasi tradisional, yakni demi tujuan keagamaan dengan aksentuasi pada aspek penguasaan grammar dan keahlian menterjemah. Untuk masa sekarang ini, system pengajaran dengan model kurikulum seperti ini tidak lagi relevan dan oleh karenanya harus segera di rubah. Sebab, kalau merujuk pada perkembangan dewasa ini bahasa arab sebagai bahasa internasional tidak lagi hanya berfungsi sebatas bahasa agama. Akan tetapi telah menjadi media komunikasi seluruh aspek kehidupan. Konsekuensinya, bahasa arab tidak lagi cukup hanya dikuasai secara pasif dalam bentuk penguasaan grammar dan keahlian menterjemah, akan tetapi harus dikuasai secara komunikatif dalam pengertian yang lebih luas, baik lisan maupun tulisan. Oleh karenanya, system pengajaran bahasa arab sudah saatnya dikembangkan dengan kurikulum pengajaran yang berorientasi modern. Yakni kurikulum yang dirancang dengan muatan dan unsure- unsure yang lengkap sebagai sebuah system pengajaran sertamengarahkan pengajaran bahasa arab untuk tujuan yang mendukung perannya dizaman sekarang ini.